"Special Circumstances" and the Politics of Climate Vulnerability: African Agency in the UN Climate Change Negotiations. Issue 3 (December 2021) - Chan, Nicholas
African countries are well recognised as being among the worst affected by the impacts of climate change. However, efforts to secure recognition of these "special circumstances" of African countries within the UN climate negotiations have been unsuccessful, despite this being a continental priority prior to and following adoption of the Paris Agreement. Such status is linked to global priorities for funding adaptation to climate change. This article explores why some other groups of developing countries have been successful in securing such recognition when African countries have not. It provides a historical institutionalist explanation of the path-dependent politics of such institutional recognition, emphasising the timing of when different groups have advanced vulnerability claims, which shapes the opposition that African countries have encountered in their efforts, as relative late-movers, to exercise agency. It highlights contestation surrounding what "vulnerability" to climate impacts means, and how this contestation has divided Global South solidarity.